2007
DOI: 10.1177/0164027507305731
|View full text |Cite
|
Sign up to set email alerts
|

Deriving a Model of the Necessity to Hospitalize Nursing Home Residents

Abstract: Although often important to recover from acute medical problems and exacerbations of chronic illness, hospitalizations can be traumatic for nursing home residents and costly for payers. It is important that unnecessary hospitalizations are avoided wherever possible. The authors derived and validated a diagnosisbased model to estimate the clinical necessity of hospitalizing nursing home residents with common conditions using data from an expert panel survey. Model validation involved a linked minimum data set-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Using a model of the clinical necessity of hospitalization (O'Malley et al 2007), we found that the predicted proportion of potentially preventable hospitalizations (those with a low predicted necessity of hospitalization) for a nursing home had little predictive power and we consequently excluded it from the models.…”
Section: Discussionmentioning
confidence: 99%
“…Using a model of the clinical necessity of hospitalization (O'Malley et al 2007), we found that the predicted proportion of potentially preventable hospitalizations (those with a low predicted necessity of hospitalization) for a nursing home had little predictive power and we consequently excluded it from the models.…”
Section: Discussionmentioning
confidence: 99%
“…A large literature has suggested that a substantial portion of hospital admissions of nursing home residents can be avoided through careful management of these conditions in the nursing home (O'Malley et al. ; Grabowski et al. ; Ouslander et al.…”
Section: Methodsmentioning
confidence: 99%
“…sepsis, meningitis, endocarditis), gastrointestinal bleeding, and stroke appendectomy. 26,29 The third outcome variable was defined as any discretionary hospitalization from a NH within a 180-day window after the baseline date. We considered a hospitalization as discretionary when there is no clear agreement in the necessity of hospitalization for the medical condition (i.e.…”
Section: Methodsmentioning
confidence: 99%